PELAYANAN EAZY PASSPORT DALAM MEWUJUDKAN GOOD GOVERNANCE PADA KANTOR IMIGRASI KELAS I TPI BANDAR LAMPUNG - Hendrick Alif Arsyandy; Rahmawati Nurul Jannah; Gunawan Ari Nursanto (Journal of Administration and International Development, 2022)
The Directorate General of Immigration as the spearhead of the agency responsible for immigration in Indonesia is obliged to improve the implementation of a series of immigration activities in order to achieve public satisfaction with transparency in the field of immigration services, accountability and high responsiveness in handling incoming complaints from the public. Because the level of satisfaction from the community towards immigration officers is a reference and an important factor that needs to be considered in immigration services. In this case, the existing quality improvement can be in the form of innovations made in each UPT Dirjenim itself. One of the innovations is shown by the existence of the Eazy Passport service. Eazy Passport is a form of service provided by the immigration office work unit to fulfill the immigration function, namely immigration services. The Eazy Passport facility is a passport issuance service that is carried out collectively outside the immigration office with a minimum requirement of 20-25 applicants. In order to achieve optimal service, it is closely related and becomes the main thing for the realization of Good Governance in the work area of the immigration office. The service itself can be described as an effort to serve the needs of others who get rewards or services. Good governance itself aims to reform the bureaucracy to organize a system that regulates the implementation of a quality, effective and efficient Kemenkumham organization, so that it is able to provide appropriate, efficient, and professional services to the community. In this study, used descriptive qualitative research methods. A research method related to the social sciences that collects and provides analysis related to research subject data both in behavior, motivation, action by way of description in the form of words and language specifically that utilizes various scientific methods. The conclusion in this study is in the form of an Eazy Passport service which aims to prevent Covid-19 in the work environment of the Class I Immigration Office of TPI Bandar Lampung to prioritize Eazy Passport services in order to suppress clusters or the spread of positive cases of Covid-19 in the office environment and to realize optimal services. to support the achievement of good governance.